Serum and brain metabolomic study reveals the protective effects of Bai-Mi-Decoction on rats with ischemic stroke - Lingling Yang; Xiaojuan Su; Fangfang Lu; Rong Zong; Shuqin Ding; Jing Liu; Gidion Wilson; Liuyan Li; Youyue Yang; Weibiao Wang; Xiaoying Wang; Jianyu Chen; et al. (Frontiers Media S.A., 2022)
Bai-Mi-Decoction (BMD), which is composed of Eugenia caryophyllata, Myristica fragrans, Moschus berezovskii, and Crocus sativu, is a characteristic TCM multi-herb formula for brain disease. However, the mechanism of protective effects of BMD on ischemic stroke (IS) still has not been clarified. Our study is designed to elucidate the protective effects and underlying mechanisms of BMD on IS by employing pharmacodynamic and serum and brain metabolomic methods. In this experiment, 90 adult male Sprague-Dawley rats were randomly divided into the sham operation group (SHAM, vehicle), middle cerebral artery occlusion-reperfusion injury model group (MCAO/R, vehicle), positive control group (NMDP, 36 mg/kg/day nimodipine), and low (BMDL, 0.805 g/kg/day), moderate (BMDM, 1.61 g/kg/day), and high (BMDH, 3.22 g/kg/day) dosage of BMD prophylactic administration groups. The drugs were dissolved in 0.5% CMC-Na and orally administered to rats with equal volumes (100 g/ml body weight) once a day for 14 consecutive days. Neurological deficit score, cerebral infarct volume, change in body weight, and serum NO, SOD, MDA, GSH, and GSSG levels were determined. Pathological abnormalities using hematoxylin and eosin staining and the expression of VEGF, caspase-3, and NF-κB were analyzed. Furthermore, serum and brain metabolic profiles were explored to reveal the underlying mechanism using UHPLC-QTOF-MS/MS technology. BMD exhibited significant neuroprotective effects on MCAO/R rats. As compared to the MCAO/R model group, it could reduce the neurological deficit score and cerebral infarct volume, increase body weight, enhance GSH, SOD, and GSSG activities, and decrease NO and MDA contents of MCAO/R rats. Meanwhile, BMD could ameliorate pathological abnormalities of MCAO/R rats through reducing neuronal loss, vacuolated spaces, shrunken neurons, and destructed neuron structure, as well as regulating the expression of VEGF, caspase-3, and NF-κB. UHPLC-QTOF-MS/MS-based serum and brain metabolomics analysis found a total of 53 differential metabolites between MCAO/R and SHAM groups, of which 30 were significantly regulated by BMD intervention, and further metabolic pathway analysis implied that the protective effects were mainly associated with amino acid and glycerophospholipid metabolisms. Our pharmacodynamic and metabolomic results revealed the neuroprotective effects of BMD on MCAO/R rats, and the underlying mechanisms were probably related to amino acid and glycerophospholipid metabolisms.